Analysis of Insurance Service Product Claim Submission at PT. Prudential Syariah Binjai Branch - Nelsi Agustina Siburian; Fauzi Arif Lubis (Jurnal Ekonomi, Manajemen, Akuntansi dan Keuangan, 2022)
PT. Prudential Syariah Branch Binjai is an Indonesian insurance company whose mission is to provide future welfare and health through various products, including life and health insurance. The purpose of this study was to determine how to submit a claim for life and health insurance at PT. Prudential Syariah Binjai Branch. The qualitative research methodology used in this final project includes surveys and interviews. Insurance claims are replaced or dissolved if the standards met are properly met, according to research. Notification, Document Attachment, Rejection, Claim Approval, or Claim Payment are the steps in filing a claim. The conclusion of this study is the method of insurance claims at PT. The life and health insurance products of the Prudential Syariah Binjai branch are in compliance with applicable laws and are handled properly by agents or customer service, although the procedure must be changed to make it easier and faster.